What is the publication rate for presentations given at the British Academic Conference in Otolaryngology (BACO)?. (25th July 2016) - Lau, A.S.; Adan, G.H.; Krishnan, M.; Leong, S.C.
Abstract : Objectives: The publication rate of some large academic meetings such as the American Academy of Otolaryngology‐Head and Neck Surgery has been reported as 32%. We aimed to compare the rate of publication at the British Academic Conference in Otolaryngology (BACO) to allow surveillance of research activity in the United Kingdom (UK). Design and setting: The abstract records of both BACO 2009 and 2012 were examined. The MEDLINE database was searched using PubMed (http://www.ncbi.nlm.nih.gov/pubmed ) and an iterative approach. We recorded time to publication as well as the authors' region and journal. Main outcome measures: publication rate by conference, region and journal. Results: Twice the number of presentations were made at BACO 2012 ( n = 814) compared to BACO 2009 ( n = 387). Absolute numbers of publications were 158 in 2012 and 92 in 2009. Overall, the publication rate dropped from 24% overall in 2009 to 19% in 2012. This difference in proportions was not significant ( P = 0.08). The number of abstracts accepted for BACO 2012 doubled from BACO 2009 in nearly every subspecialty category, except the general/training category, which trebled. For both conferences, head and neck was the largest subspecialty abstract category, as well as the largest subspecialty publication category. Conclusions: This study showed that the majority of abstracts presented at BACO 2009 and 2012 did not progress to publication. The rate of publication was similar to that seen in other general ENT meetings but do not compare favourably to the 69% rate seen for presentations made at the Otorhinolaryngological Research Society (ORS). The large increase in accepted abstracts at BACO 2012 may reflect growing competition for entry to specialist training.